Novel hybrid machine learning optimizer algorithms to prediction of fracture density by petrophysical data; Journal of Petroleum Exploration and Production; Vol. 11, iss. 12 - Rajabi M. Meysam; Beheshtian S. Saeed; Davoodi Sh. Shadfar; Ghorbani H. Hamzeh; Mohamadian N. Nima; Radwan A. E. Ahmed; Ahmadi A. M. Alvar Mehdi (2021, 2021)
Title screen